PENGEMBANGAN UMKM DENGAN MODUL ILO SCORE: PENGEMBANGAN UMKM DENGAN MODUL ILO SCORE PADA WARKOP ICHA DI KABUPATEN BENGKAYANG - Yasinta, Yasinta (Universitas Kristen Immanuel, 2023)
ABSTRACT This study aims to help MSME actors to be able to develop and compete in a healthy manner in times of rapid development from time to time. In this case, the Shanti Bhuana Institute Academics conducted a survey to determine where they would carry out mentoring and apply the knowledge they got during their lectures, by choosing the type of MSMEs that were quite popular in the city of Bengkayang, we from the Academics side chose to accompany Warkop. Warkop is a business engaged in the MSME sector that sells various drinks and other snacks. The location of the Warkop that we accompany is in the city of Bengkayang, West Kalimantan, this Warkop was established on February 25, 2022. There are several problems encountered in this Warkop MSME, among others, the arrangement of goods is not well organized, the arrangement of goods is not based on labels, there is no menu list so that consumers who visit cannot choose what they drink easily, there is no business name or brand yet. Based on the problems that have been explored from the MSMEs, it can be seen that this occurs because of the limitations possessed by the business owners, therefore it is necessary to have support and assistance for the empowerment of MSMEs in the Warkop in order to develop MSMEs, therefore the Shanti Bhuana Institute has sent one of the Academics to assist the Warkop with the aim of making the Warkop one of the SMEs that developed in Bengkayang district through the application of the ILO SCORE module. Keywords: Layout, ILO SCORE, SMEs, Consumers, Bengkayang